Tingkat Kemampuan Smash Bola Voli Pada Atlet Voli Klub Bina Putri Medan - Andi Nata Purba (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
The purpose of this study was to determine the level of smash ability of the Bina Putri Volleyball Club in Medan athletes as they are without prior treatment. This research is a descriptive study with a population of 10 people with a sampling technique using a total sampling technique which means the number of samples is 10 people. The instrument used to measure smash ability is the Nurhasan smash attack instrument. From the tests carried out, the results obtained from the athlete's smash ability with an average score of 6.6. The average score obtained shows that the smash ability of the athletes of the Bina Putri Volleyball Club in Medan is included in the poor category with a score of 2. One of the factors causing the low smash ability of the athletes of the Bina Putri Volleyball Club in Medan is the weakness of the explosive power of the leg muscles of the athletes. These results indicate that it is necessary to carry out exercises aimed at increasing the explosive power of the leg muscles on a regular and continuous basis in an effort to increase the explosive power of the leg muscles.